Serum irisin: A potential diagnostic marker for insulin resistance in acne vulgaris - Lin Tang; Bei Yu; Yongmei Liao; Siqi Long; Haoxiang Yan; Qingqing He; Changqiang Li (Wolters Kluwer Medknow Publications, 2022)
Background: Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous unit. Many factors are involved in the occurrence of acne. It has been confirmed that some adipokines play an important role in the development of AV. Irisin is a novel adipokine, which is highly expressed in skeletal muscle, liver, and fat. It improves insulin resistance (IR) by inducing the browning of white adipose tissue, increasing heat production and energy expenditure. Objective: The purpose of this study was to investigate the role of serum irisin as an adipokine to explore its function in the pathogenesis of AV and its correlation with IR, and whether it can be used as a potential biomarker of insulin sensitivity. Although the hyperinsulinemic-euglycemic clamp remains the gold standard for accurate determination of IR, it cannot be performed routinely. Various alternative simpler measures have been used, the most common being homeostasis model assessment. However, these metrics are limited by their accuracy, cost, and blood collection requirements.[1] Therefore, an effective and feasible serum biomarker is an attractive and relatively straightforward method, which may provide clinicians with a more accurate and simple method for the prediction and diagnosis of IR. IR can often be detected before other symptoms appear, so establishing an early diagnosis method will allow for the appropriate treatment of patients before the disease develops. Patients and Methods: The study included 171 subjects; 115 patients with newly diagnosed AV and 56 apparently healthy subjects. The contents of irisin and interleukin-1 alpha in serum were determined by enzyme-linked immunosorbent assay. The IR index was calculated by the homeostasis model. Results: Serum irisin levels in AV patients and control group were (24.0 ± 11.3) and (104.3 ± 27.0) ng/dl, respectively, which were significantly lower than those in control group (P < 0.001). Serum irisin was negatively correlated with IR (r = −0.711, P 0.001). The sensitivity of irisin was 100.0%, the specificity was 92.8%, and the cutoff point was 53.32. The decrease of serum irisin level could predict the patients with IR in acne. Conclusion: Serum irisin levels in AV patients were significantly decreased. Serum irisin showed acceptable performance criteria in the diagnosis of AV with IR. Serum irisin seems to be a good diagnostic and prognostic marker for IR. Further multi-center studies are needed to confirm this link, which could pave the way for new treatment options.